2018
DOI: 10.1111/ors.12355
|View full text |Cite
|
Sign up to set email alerts
|

A comparative clinical study between the efficacy of Nd:YAG laser and Diode laser in the management of physiologic gingival melanin pigmentation

Abstract: Objective Recently, laser surgery has been used extensively in the treatment of gingival melanin pigmentation (GMP). Several lasers have been utilised for this purpose. This study compares the use of Nd:YAG and diode in treating of GMP based on healing period, recurrence and patient’s acceptability. Materials and Methods Twenty patients with moderate/severe GMP were included in this split mouth study. Nd:YAG with a free running pulse mode, wavelength of 1064 nm, was used to treat GMP of the two right quadrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…Our findings indicate that there was a significant reduction in pigmentation scores following treatment. These results were consistent with other published studies (11,(17)(18)(19)(20)(21). Gul et al (2019) conducted a systematic review and meta-analysis examining the optimal approach for managing physiologic gingival hyperpigmentation, various depigmentation methods, including lasers, were evaluated.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings indicate that there was a significant reduction in pigmentation scores following treatment. These results were consistent with other published studies (11,(17)(18)(19)(20)(21). Gul et al (2019) conducted a systematic review and meta-analysis examining the optimal approach for managing physiologic gingival hyperpigmentation, various depigmentation methods, including lasers, were evaluated.…”
Section: Discussionsupporting
confidence: 86%
“…The findings indicated that diode laser was significantly more effective as compared to Erbium lasers (22). Alasbahi et al compared between the effectiveness of Nd:YAG laser and Diode laser in managing physiologic gingival melanin pigmentation, and concluded that both laser types were effective without any significant difference observed between them (18). Moreover, Moeintaghavi et al conducted a study comparing the effectiveness of CO2 and diode lasers for gingival depigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison of the Nd:YAG laser and the Diode laser in the management of physiologic gingival melanin pigmentation, it was concluded that Both Nd:YAG and diode lasers were effective in the management of physiologic gingival pigmentations. 15 Regarding using lasers for gingival depigmentation, Murthy et al reported that in general lasers are an effective and safe method for gingival depigmentation. Healing was uneventful and no repigmentation occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that laser techniques associated with less postoperative complications such as pain, bleeding, discomfort, and infection when compared to conventional surgical techniques. 16 , 28 , 29 , 30 , 31 Also, it is required to apply periodontal pack after gingival depigmentation using conventional techniques, whereas, when using lasers, there is no need for it, because a white fibrin slough will appear in the first days following the procedure, which will serve as a biological wound dressing that seals the ends of sensory nerves. 32…”
Section: Discussionmentioning
confidence: 99%